Regeneration, political economy and education in the Spanish monarchy during the eighteenth century. Concepts in the delimitation of a semantic field - Adriana MILANO (Cuadernos Dieciochistas)
During the Bourbon reforms modernization and secularization were among the bases of a general plan for remedying a situation of decay which had been detected since the previous century. In that framework, concepts such as education had significance  in the debates generated by the Spanish Enlightenment and the development of reforms. In this piece of workwe analyse the evolution in the concept of education during the eighteenth century, its relationship with the regeneration ideal and its connection with the rise of the political economy debates. The work pursues the delimitation of the semantic field in which that concept is included in connection with others, opposite or parallel, also the reforms entailed by the process of secularization and educational modernization in addition to the different forms of sociability and circulation of ideas that allowed discussions in Spain.